Quizizz Sebagai Media Untuk Memetakan Pemahaman Konsep Optika Geometri Calon Guru Fisika - Sukma, Melani Dyah Ayu; Febriani, Yuliana; Setiaji, Bayu (Universitas PGRI Semarang, 2023)
This study aims to map the understanding of geometrical optics concepts for physics teacher candidates using the Quizizz application. The type of research used is experimental research. The sample used in this study was 30 students majoring in physics education at Yogyakarta State University as a control class. The research method used is the questionnaire method. Instruments used in the form of multiple-choice questions. Data obtained were analyzed by CRI (Certainty of Response Index) techniques and inferential statistics (Test-t). The results of the study are described that the highest misconception using Quizizz is in the number 6 questions with the indicator of the shadow properties produced by microscope, whereas without using Quizizz there are questions number 5 with a magnification indicator on the lup. Based on the results of the study it can be concluded that there is no prescription the level of understanding of the concept of students when using Quizizz and without Quizizz.Keywords: misconceptions, students, geometry optics, Quizizz